THREE GENERATION, THREE WOMEN, THREE CHILDHOOD: GAZIANTEP SAMPLE - Cihan ARDİLİ (Fırat University, 2019)
Childhood sociology defines childhood as a socially structured process, and an area worthy of study because of a child being a competent and social actor and the special and unique importance of being a child. For this reason, a child has biologically universal characteristics, but childhood is partial (not singular). In this study, childhood experience of three generations of women (grandparents, mothers, girls) differing from historical and cultural periods are discussed. Intergenerational childhood experiences of three generations of women, of whom three settled in Gaziantep and three migrated to Gaziantep, have focused on. In this study using in-depth interview method, the interviews were conducted within the framework of semi-structured questions that set out the cultural, social and historical context, such as childhood, daily life practices, parental relations, physical and social environment, gender differences experiences, friendship forms, definition of childhood, individual decision making, relationship with technology and use of space. At first sight, childhood, defined as a vital category, refers primarily to an identity and a status. This identity and status, in every aspect, should not be considered and assessed independently of the current time frame / context. Just as in other categories of life, childhood experience is surrounded by the characteristics of this time period. The intergenerational childhood experience, which is the main axis of this study, shows that childhood, particularly in social context, is neither a complete break nor a full adoption. In this sense, because childhood has a different character in each generation, the fact that the child and childhood are social actors is one of the main arguments of this study. This study aims to contribute to the development of a sociological understanding of childhood by tracing the differences in childhood experiences.